DEVELOPING ENGLISH VOCABULARY APPLICATION FOR THE MENTALLY-RETARDED STUDENTS AT SLB ARYA SATYA HATI - Asrita Annisa; Barotun Mabaroh; Rasyidah Nur Aisyah (Prodi Tadris Bahasa Inggris, 2021)
The aim of this study was to develop the application of English Vocabulary Application based on the desktop version to assist the mentally-retarded students in learning English vocabulary. This research used Research and Development (R&D) with ADDIE models. This research involved 5 seventh-grader of mentally-retarded students and 3 teachers who teach mentally-retarded students from SLB Arya Satya Hati. The researcher used three instruments for this research: (1) Interview, (2) Questionnaire, and (3) Documentation. The data were analyzed by using Arikunto’s theory (2010) and percentage index (%). The researcher carried out the dissemination by uploading the video on how to operate the English Vocabulary Application on Youtube due to the COVID-19 pandemic. From the validation results, it showed that English Vocabulary Application was feasible to be used as a learning media in assisting the mentally-retarded students with 100% materials validation results and 95% programming validation results. Based on the application try-out, 4 MR students could guess more than 10 words of 20 words and 1 MR student guessed 8 words of 20 words. Based on this research, the English Vocabulary Application could be used in teaching- learning vocabulary for mentally-retarded students through ICT. This application could be used as one ICT learning media and the other researcher could develop this application with the newest features. Keywords: English Vocabulary Application, Mentally-Retarded students, teaching vocabulary